China's contemporary image and rhetoric practice - Wei, Weixiao (Abingdon, Oxon ; New York, NY : Routledge, 2021)
"China's Contemporary Image and Rhetoric Practice ushers in an overview of Chinese diplomatic rhetoric, paves a way to depicting the image of China with western lens, makes a profound shift in domestic perspective of this image, and reveals new sites for Chinese rhetoric to serve as the deepening and widening topics of relevant studies of Chinese literature, Chinese discourse analysis, Chinese sociology, Chinese politics and so on. These cherry-picking chapters are at a premium and may facilitate the expanding development of Chinese studies. This book is a valuable reference for scholars, researchers and graduate or postgraduate students in Chinese linguistic and social studies"--
OCLC-licensed vendor bibliographic record.
Keywords: Rhetoric -- Political aspects -- China; Rhetoric -- Social aspects -- China; Discourse analysis -- Political aspects -- China; Discourse analysis -- Social aspects -- China; China -- Relations; LANGUAGE ARTS & DISCIPLINES / General; LANGUAGE ARTS & DISCIPLINES / Journalism; LANGUAGE ARTS & DISCIPLINES / Linguistics